(untitled) (Politeja, 2018)
Beyond Geopolitics. The Sino-Russian Relations in the Late 2010s Since more than a decade the international (Western) academia has been considering Sino‑Russian relations as an „Axis of Convenience”: a temporarily, shallow, tactical alliance prone to changing circumstances; a one that may turn into antagonism should international situation evolve. This approach reached its climax after Donald Trump’s victory in US Presidential elections in 2016: many believed that there would soon be „a reverse Nixon’s strategy”. The reality has falsified these theses and showed that Sino‑Russian relations have solid foundations. These more stable base of Russia‑China relations was born in late 2000s when Russian ruling elite made a choice and decided that China did not pose a threat to current Russian regime. This elite’s understanding paved a way for current Sino‑Russian rapprochement.